The Effect of the Growth Mindset and Campus Environment on Cadet Academic Performance - Hasnur, Juliandri; Wirza, Elfira; Dwi Yatno, Langandriansyah (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
Cadets’ academic performance is commonly influenced by internal and external factors. The internal factor that mostly influences cadets’ academic performance is growth mindset, meanwhile the external factor is campus environment. The purpose of this study was to find out the effect of growth mindset and campus environment on cadets' academic performance. This study is a quantitative study with an ex-post facto method. The research instrument was a questionnaire given to 100 participants. The data analysis technique used multiple linear analysis by using SPSS application. The results of the study showed that there was a positive effect of growth mindset and campus environment on cadets' academic performance. From the results of this study, it can be recommended that in order to improve cadets' academic performance, the learning curriculum must be able to develop cadets' thinking skills, and the campus environment must be conducive and supportive. Furthermore, institutions are advised to organize course or training programs that focus on developing cadets' thinking skills, so that cadets can be more proactive in learning activities and have growth mindset for the future. Although this study has been conducted optimally, there are several limitations that can be used as recommendations for future research. This study used a quantitative approach, further researchers are advised to use a qualitative or mix-method approach to explore more deeply the relationship between these three variables. In addition, further research needs to consider other factors that influence cadets' academic performance, such as intrinsic motivation, teaching quality, and family support.